Writing groups inside and outside the classroom - Moss, Beverly J.; Nicolas, Melissa; Highberg, Nels Pearson (International Writing Centers Association (IWCA) Press Series., 2004)
Showing that writing groups function first and foremost as literary events, this work argues for writing groups to be seen contextually. One can then begin to comprehend the different types of collaboration that take place in writing groups across setting and communities.